DL-3-n-butylphthalide improves cerebral hypoperfusion in patients with large cerebral atherosclerotic stenosis: a single-center, randomized, double-blind, placebo-controlled study - Chen, Dawei (BMC Neurol, 2020)
BACKGROUND: DL-3-n-butylphthalide (NBP) was demonstrated to increase the cerebral blood flow (CBF) in the animal models, but there are no clinic studies to verify this. We aimed to explore the effect of NBP on improving cerebral hypoperfusion caused by cerebral large-vessel stenosis. METHODS: In this single-center, randomized, double-blind, placebo-controlled study, 120 patients with severe carotid atherosclerotic stenosis and cerebral hypoperfusion in the ipsilateral middle cerebral artery (MCA) were included and randomly assigned into NBP or placebo group as 1:1 radio. Patients in NBP or placebo group received 200 mg or 20 mg of NBP capsules three times daily for four weeks respectively. Single photon emission computed tomography (SPECT) was used to assess regional CBF (rCBF) in four regions of interest (ROIs) corresponding to MCA before and 12 weeks after the treatment. After therapy, the rCBF change for every ROI and the whole CBF change in MCA territory for every patient were classified into amelioration, stabilization and deterioration respectively. RESULTS: 48 NBP patients (6 with bilateral stenosis) and 46 placebo patients (8 with bilateral stenosis) completed the trial. Overall, both groups had 54 stenotic carotid arteries and 216 ROIs for rCBF change analysis. After therapy, the rCBF in ROIs increased in NBP group (83.5% ± 11.4% vs. 85.8% ± 12.5%, p = 0.000), whereas no change was found in placebo group (86.9% ± 11.6% vs. 87.8% ± 11.7%, p = 0.331). Besides, there was higher percentages of ROIs with rCBF amelioration and stabilization in NBP group than in placebo group (93.1% vs. 79.2%, p = 0.000). Furthermore, ordinal regression analysis showed that compared with placebo, NBP independently made more patients to have whole CBF amelioration in ipsilateral MCA (Wald-χ2 = 5.247, OR = 3.31, p = 0.022). CONCLUSIONS: NBP might improve the cerebral hypoperfusion in the patients with carotid artery atherosclerotic stenosis. TRIAL REGISTRATION: Chinese Clinical Trial Registry, ChiCTR1900028005, registered December 8th 2019- Retrospectively registered (http://www.chictr.org.cn/index.aspx).